Estrogens increase the expression of fibulin-1, an extracellular matrix protein secreted by human ovarian cancer cells. - Clinton, G M (1996)
Ovarian cancers have a high ability to invade the peritoneal cavity and some are stimulated by estrogens. In an attempt to understand the mode of action of estrogens on these cancer cells and to develop new markers, we have characterized estrogen-regulated proteins. This study was aimed at identifying a protein secreted by ovarian cancer cells whose level was increased by estradiol [Galtier-Dereure, F., Capony, F., Maudelonde, T. & Rochefort, H. (1992) J. Clin. Endocrinol. Metab. 75, 1497-1502]. By using microprotein sequencing, the 110-kDa protein was identified as fibulin-1, a protein of the extracellular matrix that binds to fibronectin, laminin, and nidogen. The amount of immunoprecipitated fibulin-1 secreted into the medium and present in the cell extract was increased up to 10-fold by estradiol in three estrogen-responsive ovarian cancer cell lines. By immunohistochemistry fibulin-1 was located in the stroma of several ovarian cancers and cysts. The findings highlight a potential role for fibulin-1 in the spread of ovarian cancer in the peritoneal cavity and/or in distal metastases.